2014
DOI: 10.1016/j.seizure.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with perceived stigma of epilepsy in Croatia: A study using the revised Epilepsy Stigma Scale

Abstract: The Croatian translation of the rESS has been proved to be a suitable instrument for diagnosing epilepsy stigma. The results of our model point to the possibility that the rESS might be more sensitive than the original ESS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
0
21
1
2
Order By: Relevance
“…Ancak daha çok nöbet tipinin, nöbet sıklığının ve tedavi düzenlemesinin ön planda olduğu muayenede bu durum ihmal edilebilmektedir. [13][14][15] Bizim çalışmamızda da cinsiyet, hastalığın süresi ve nöbet sıklığı ile hastalığı gizleme durumu arasında ilişki olmadığı görüldü. Ancak gençlerde hastalığı gizlemenin daha sık olduğu, bu durumun yaş ilerledikçe azaldığı anlaşıldı.…”
Section: Discussionunclassified
“…Ancak daha çok nöbet tipinin, nöbet sıklığının ve tedavi düzenlemesinin ön planda olduğu muayenede bu durum ihmal edilebilmektedir. [13][14][15] Bizim çalışmamızda da cinsiyet, hastalığın süresi ve nöbet sıklığı ile hastalığı gizleme durumu arasında ilişki olmadığı görüldü. Ancak gençlerde hastalığı gizlemenin daha sık olduğu, bu durumun yaş ilerledikçe azaldığı anlaşıldı.…”
Section: Discussionunclassified
“…Besides, it should be kept in mind that in our study, AA group was younger when compared with MD group and it was reported that age may have a significant impact on perceived stigma. [26]…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that people with epilepsy have a high apprehension for stigma. 38,39 Adolescents with epilepsy have been recorded to get exposed to this stigmatization more compared with younger children. 40 In addition to that, patients with low socioeconomic status were reported to have higher stigma perception and lower health-related life quality.…”
Section: Factors About Child Characteristicsmentioning
confidence: 99%